Development of UV Laser Source Based on Distributed Feedback Dye Lasers Foruse in Measurement of Ozone in the Lower Atmosphere - Pham Minh, Tien; Bui Van, Hai; Duong Tien, Tho; Dinh Van, Trung (Communications in Physics, 2017)
We conducted a study to develop a transmitter consisting of two Distributed Feedback Dye Lasers (DFDL) using Rhodamine 6G as an active medium, pumped by a frequency-doubled Nd:YAG laser (5ns, 10 Hz, 532 nm). The BBO crystals are used for frequency-doubling of DFDLs to generate UV missions. This system has been set up and it generates selected wavelenghts at 282.9 nm and 286.4 nm with the energy of 30 \(μ\)J/pulse and 60 \(μ\)J/pulse respectively. A DIAL system using this UV transmitter is designed to measure the vertical distribution of ozone with high temporal and spatial resolution. Our simulations of received DIAL signal indicate that the altitude of ozone distribution measurement can reach to over 5000 m along with range resolution of 100 m.